Assessing the impact of Pseudocercospora leaf spot infection on commercially important silkworm cocoon characters - Monir, Siraj; Biswas, Mohan Kumar (Indian Journal of Plant Protection, 2026)
One of the major challenges to successful sericulture in India is the prevalence of infections in mulberry. In West Bengal, Pseudocercospora leaf spot, which is caused by [Pseudocercospora mori], is a highly frequent ailment. An investigation was conducted to determine the impact of feeding mulberry leaves infected with Pseudocercospora leaf spot on the number and quality of cocoon and silk. The silkworm larvae were fed varying grades of Pseudocercospora leaf spot infected leaves, and the rearing parameters (larval duration, length, weight, single cocoon weight, single shell weight, shell ratio, ERR wt., ERR no., mortality and biochemical analysis of leaves) were used to measure the effects of the feeding. The total larval duration increased by 4 more days due to the feeding of different graded of Pseudocercospora leaf spot leaves in comparison to 22 days in control. Decreased from 3.13 g to 0.65 g (G-IV). The larvae weight from 2.00g to 0.85g for single cocoon weight; from 0.44 g to 0.09 g for single shell weight; from 22.02% and 11.04% for shell ratio percentage; from 19.53 kg to 1.58 kg for effective rate of rearing weight and from 9266 to 1400 for effective rate of rearing number in respect of healthy and Grade-IV diseased leaves. The reduction in quality and yield of larvae was proportional to the level of disease severity. It was observed that all the biochemical properties i.e. amount of moisture, protein, chlorophyll and total sugar contents were reduced drastically in mulberry leaves due to Pseudocercospora leaf spot diseases which negatively affect the growth of larvae and cocoon.